Structural recognition of three significant C88 isomers and its chlorinated derivatives by X-ray spectroscopy. (2nd August 2020) - Ma, Yong; Zhang, Jun-Rong; Wang, Ruo-Yu; Wang, Sheng-Yu; Wang, Chuan-Kui; Song, Xiu-Neng
ABSTRACT: The structures of three important isomers and their corresponding chlorinated derivatives for fullerene C 88 are studied, and their NEXAFS and XPS spectra are stimulated at the density functional theory level. The three isomers show significant changes in the total spectra and the spectra of each component after chlorination. These six configurations can be easily identified by analyzing the dependent relationship of NEXAFS and XPS spectra to the structures, which will provide an effective theory evidence for identification of the isomers and corresponding derivatives for fullerene C 88 in future experiments. GRAPHICAL ABSTRACT: